An RANCANG BANGUN MESIN PENGAMBILAN TELUR PUYUH OTOMATIS BERBASIS INTERNET OF THINGS: Rancang Bangun Mesin Pengambilan Telur Puyuh Otomatis Berbasis Internet Of Things: Desain Sistem Mekanis dan Kinerja - Nur Assidiqin, Muhammad Hafizzin; Sakti, Arya Mahendra; Riandadari, Dyah; Arifianti, Lailatus Sa'diyah Yuniar (Jurnal Rekayasa Mesin, 2026)
Abstract: Quail farming is one of the agribusiness sectors with significant potential to meet food demands in Indonesia. However, the egg collection process, which is still carried out manually, remains a major obstacle to improving efficiency and productivity. This manual process requires considerable time and labor and poses a high risk of egg damage. These conditions lead to increased operational costs and decreased production quality. This study aims to design and develop an Internet of Things (IoT)-based automatic quail egg collection machine to reduce dependence on manual labor and enhance production efficiency. The research method employed was Research and Development (RnD), which included literature review, system design, mechanical and electronic component assembly, performance testing, and data analysis. The developed system consists of a NEMA 23 stepper motor, roller conveyor, supporting sensors, and an ESP32 microcontroller integrated with an IoT-based application. The system is designed to enable automatic egg collection and allows remote monitoring and control via an internet network. The results indicate that the automatic quail egg collection machine performs optimally at a motor speed of 40 rpm with an operating time of one minute. Under these conditions, the system achieves a success rate of 98–100% with a cage capacity of 50 quails and a storage capacity of 100 eggs. Furthermore, the implementation of IoT technology enables real-time monitoring and control, thereby improving operational efficiency and ease of farm management. Therefore, the developed machine is proven to enhance productivity, reduce manual workload, and support the application of automation technology in the quail farming sector in Indonesia. Keywords: design and development, automatic machine, egg collection, Internet of Things, quail.